ABOUT LEGALIZATION OF EXHAUST (MAINING) CRYPTOCURRENCY BY THE TYPE OF ECONOMIC ACTIVITY - B.V. Derevyanko; O.A. Turkot (Економіка та право, 2018)
In Ukraine, the cryptocurrency is viewed as a monetary surrogate. In many countries of the world, operations with cryptocurrency are more or less permitted. You can name countries such as Australia, Austria, Bulgaria, Brazil, Israel, Canada, China, Norway, Singapore, USA, Thailand, Germany, Croatia, Switzerland, Japan and others. On the basis of objective analysis and the study of examples from foreign experience, the legal regime of operations with the cryptocurrency is proposed to equalize with the legal regime of operations with foreign currency; legalize the mining of the cryptocurrency as a type of economic activity, introduce its licensing and taxation of income from it. Citizens of Ukraine are not forbidden to keep savings in foreign currency and exchange foreign currency for hryvnia and other foreign currency. Ukrainians can not receive wages or any remuneration in foreign currency on the territory of Ukraine, but they can earn or win foreign currency on the Internet. The same regime should receive cryptocurrency. And operations on mining of cryptocurrency should be licensed as highly profitable and requiring a special knowledge and skills type of economic activity. Applying income tax to miners is offered on general terms. Three ways of determining the amount of taxes are proposed: 1) granting access to representatives of the fiscal body to the computer program and purses of the cryptocurrency; 2) through the calculation by the representatives of the fiscal body of the average monthly volume of production of units of crypto currency for a certain equipment and, accordingly, in proportion to it, the amount of tax; 3) in proportion to the amount of electricity spent. The last two look the most real. In the case of taxation of operations on «mining» of cryptocurrencies, the state through the amount of electricity consumed can identify and control miners. It is concluded that the legalization of the state of the budget.